Applied E-Studies and Traditional Studies to Rise the Motivation of 1-St Year University Students - Ratniece, Dace; Cakula, Sarma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
On-line education is quickly becoming a prominent and important piece of the education. There are four types of On-line education: online, web facilitated, blended/hybrid, traditional. Because online type of education is very popular way of communication among universities students and between student and teacher, it would be perfect kind to motivate students, especially in the 1st year, who, apart from reduced study fees, require extra motivation and moral support from educators. The goal of the paper is to research optimal proportion between traditional teaching and using digital technologies influencing on student motivation.